The Effect of Giving Iron Tablets With Lemon and Honey on Hemoglobin Levels in Adolescent Girls - Abidah, Siska Nurul; Handayani, Nanik; Maharani, Uke; Handayani, Nur Maya (Napande: Jurnal Bidan, 2025)
Background: Adolescent girls lose iron during menstruation, coupled with their increased consumption of plant-based foods, resulting in insufficient iron intake to meet their daily iron needs. This leads to anemia in adolescent girls. Therefore, iron supplementation is necessary to address anemia in adolescents. The purpose of this study was to determine the effect of administering Iron tablets with lemon and honey on hemoglobin levels in adolescent girls. Method: The research design uses a pre-experimental approachone-group pretest-posttest design. A sample of 23 respondents with the techniquetotal sampling. The instrument used was an Hb level tester, a Standard Operating Procedure (SOP), and an observation sheet. Data analysis used the test Wilcoxon. Results: The results of the study were obtained from 23 respondents before giving Iron tablets with lemon and honey, most of whom experienced moderate anemia, namely 14 respondents (60.8%). After giving Iron tablets with lemon and honey, some respondents did not experience anemia, namely 19 respondents (82.61%). The results of the statistical Wilcoxon test, p=0.001 <α=0.05, show that there is an effect of consuming Iron tablets with lemon and honey on hemoglobin levels in adolescent girls. Conclusion: Consuming iron tablets with lemon and honey is very beneficial in increasing hemoglobin levels in adolescent girls. It is hoped that the provision of iron tablets to adolescent girls can be expanded to reduce the incidence of anemia in them